Factors that Influence University Students toward Customer Satisfaction and Customer Loyalty at Starbucks in Malaysia - Oh, Zi Jian; Lew, Tek Yew; Teik, Saw Wei; Elangoh, Sarveena A/P; Shen, Ze Bin; Shoo, Yee Wen; Kee, Daisy Mui Hung (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
Malaysians are among Starbucks' most devoted customers. Customer satisfaction may appear to be an elusive term that is impossible to track. Yet, some factors influence whether customers are happy, and a variety of measurement tools consistently evaluate customer satisfaction and loyalty to Starbucks. This study examines the factors influencing customer satisfaction and customer loyalty at Starbucks in Malaysia. In this study, data was gathered using internet sources and questionnaires. This survey included a total of 150 university students who had visited Starbucks. Descriptive statistics and inferential statistics were used to analyze the data. This study's findings are expected to suggest the essential qualities to emulate and increase customer satisfaction and loyalty.